Temporary Seizure under the Jordanian Defense Law and its Impact on the Right to Property: A Critical Analytical Study - Zahida جمانة يحيى صالح (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: The study aims to determine the legal means followed by the administration to expropriate property and clarify the legal guarantees provided by the Jordanian Defense Law to protect private property that received constitutional protection. The study will investigate the adequacy of these guarantees through the procedures followed by the administration in the temporary seizure and compensation for the seizure, and the extent of judicial control over the administration’s procedures in the temporary appropriation and compensation for seizure. Methods: A critical and analytical approach were applied to the texts related to the subject of the study. Results: The study finds weakness of the legal guarantees in the text of Article (5) of the Jordanian Defense Law. The assessment of compensation in case of necessity is after the seizure of possession, that is, immediate possession is permissible before the assessment of compensation. Conclusions: The study recommends the reformulation of Article (5) of the Jordanian Defense Law in line with the requirements of the constitutional principle “the right of property is safeguarded.” It also has to be reformulated, especially with regard to the period offered in it, and setting a maximum period for the seizure to ensure the protection of the right of private property from abuse by the administration. Re-drafting the text of Article (9) of the same law to clarify the procedures for compensation and the mechanism for paying it. Finally, we hope that the jurisdiction of the Administrative Court will extend to requests for compensation, as they arise from the seizure decision.